2008
DOI: 10.1523/jneurosci.5510-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Causal Role for Brain-Derived Neurotrophic Factor in the Homeostatic Regulation of Sleep

Abstract: Slow-wave activity (SWA), the EEG power between 0.5 and 4 Hz during non-rapid eye movement (NREM) sleep, is one of the best characterized markers of sleep need, because it increases as a function of preceding waking duration and decreases during sleep, but the underlying mechanisms remain unknown. We hypothesized that SWA is high at sleep onset because it reflects the occurrence, during the previous waking period, of widespread synaptic potentiation in cortical and subcortical areas. Consistent with this hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(197 citation statements)
references
References 50 publications
6
190
1
Order By: Relevance
“…We have posited that activity within cortical column neuronal circuits increases production of cytokines and neurotrophic growth factors and these factors in turn initiate localized state changes . Recently Faraguna et al (2008) demonstrated that a unilateral microinjection of BDNF into the cortex increases slow wave activity locally, which supports this hypothesis.…”
Section: Discussionmentioning
confidence: 62%
“…We have posited that activity within cortical column neuronal circuits increases production of cytokines and neurotrophic growth factors and these factors in turn initiate localized state changes . Recently Faraguna et al (2008) demonstrated that a unilateral microinjection of BDNF into the cortex increases slow wave activity locally, which supports this hypothesis.…”
Section: Discussionmentioning
confidence: 62%
“…It may, thus, contain a major gene contributing to sleep-wake regulation. TrkB is the high-affinity receptor for brain-derived neurotrophic factor (BDNF) (Luikart and Parada, 2006), and recent findings in rats suggest that BDNF secretion is causally related to sleep homeostasis (Faraguna et al, 2008;Huber et al, 2007).…”
Section: G>a Polymorphism Of Brain-derived Neurotrophic Factor (Bdmentioning
confidence: 99%
“…5,6 Moreover, in rats and humans, procedures presumably leading to synaptic potentiation or depression result in SWA increases and decreases, respectively. [7][8][9][10][11][12] More specifically, a study in humans using highdensity EEG found that performing a visuomotor learning task produced a local increase in SWA during subsequent sleep. 7 The increase was restricted to the right parietal cortical areas presumably modified by learning.…”
Section: Sleep Is Present and Homeostatically Regu-lated In All Animamentioning
confidence: 99%